SUBJECTIVE WELL-BEING AND PSYCHOLOGICAL HEALTH OF TEACHERS: SOME THEORETICAL AND PRACTICAL ASPECTS - Olena BONDARCHUK (Moldova State University, 2021)
The article deals with the problem of the correlation between subjective well-being and psychological health of teachers. It is shown that the problem of the relationship between subjective well-being and health in general is characterized by both potentially extremely important findings, and also by pivotal research issues and questions. The basic principles of the study of psychological health are determined. The main criteria and indicators of psychological health are highlighted. Groups of factors of subjective well-being of teachers that are directly related to their psychological health are identified. Distinctive features of teachers that can negatively affect their psychological health and subjective well-being are identified. The expediency of monitoring the subjective well-being of teachers as an important condition of identifying and maintaining their psychological health in the extreme conditions of nowadays is shown.   STAREA DE BINE ȘI SĂNĂTATEA MENTALĂ LA CADRELE DIDACTICE:       ASPECTE TEORETICE ȘI PRACTICE Este abordată problema ce vizează relația dintre percepția stării de bine și sănătatea mentală la cadrele didactice. Sunt evidențiate rezultate foarte importante privind relația dintre percepția stării de bine și sănătatea mentală, fiind trasate câteva direcții și probleme de cercetare în acest sens. În același context, au fost identificate principiile de investigare a sănătății mentale, criteriile și indicatorii acesteia, inclusiv factorii care determină relația dintre starea de bine și sănătatea mentală la cadrele didactice. Se mai arată care sunt condițiile specifice ce pot afecta în sens negativ sănătatea mentală și starea de bine, autorul concluzionând că, în condițiile actuale, monitorizarea stării de bine reprezintă un aspect esențial în vederea menținerii sănătății mentale a cadrelor didactice.